2021
DOI: 10.1002/ehf2.13323
|View full text |Cite
|
Sign up to set email alerts
|

Women with peripartum cardiomyopathy have normal ejection fraction, but abnormal systolic strain, during pregnancy

Abstract: We report a case series of six women with peripartum cardiomyopathy (PPCM) who incidentally underwent echocardiography prior to the clinical presentation of PPCM. For comparison, we identified controls, matched 2:1 on age, race, body mass index, gestational age, and hypertensive disorder. Among the six cases, all were diagnosed with PPCM during the post-partum period. Pre-PPCM echocardiograms were performed between 17.7 weeks of gestation and 13 days post-partum. Baseline left ventricular ejection fraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“… 19 Among these strain values, GCS index is a sensitive parameter for regional myocardial function. Tamrat et al 20 reported a significant fall in GCS among pregnant women with peripartum cardiomyopathy in spite of normal ejection fraction and left ventricular end-diastolic diameter. Additionally, GLS exhibited a drop in comparison with controls, but this reduction was nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Among these strain values, GCS index is a sensitive parameter for regional myocardial function. Tamrat et al 20 reported a significant fall in GCS among pregnant women with peripartum cardiomyopathy in spite of normal ejection fraction and left ventricular end-diastolic diameter. Additionally, GLS exhibited a drop in comparison with controls, but this reduction was nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…First, the transgenic expression of Gαq was supraphysiologic, raising the possibility that the observed mechanism of cardiomyopathy is not relevant to human disease (transgenic lines with less induction of Gαq expression revealed no phenotype). Second, the transgenic mice revealed significant systolic dysfunction at baseline, even in the absence of pregnancy, whereas such dysfunction is not seen in women with PPCM, 139 and indeed the absence of such preexisting dysfunction is included in the definition of PPCM. This model was thus important as a first demonstration that pregnancy could accelerate cardiomyopathy in mice, but the model has not been used further.…”
Section: Cardiac Expression Of Gαqmentioning
confidence: 95%
“…It can assess for complications of PPCM such as left ventricular thrombus and provide prognostic data [19 ▪ ]. However, it should be noted that LVEF and LV dimensions are largely normal during pregnancy in women who go on to develop PPCM and these changes can occur acutely or shortly after diagnosis [21 ▪▪ ]. On echo, LVEF <30% at diagnosis leads to worse prognosis, reduced rates of recovery and increased risk of adverse effects [3,20 ▪▪ ].…”
Section: Step 3: Extra (Selected Patients)mentioning
confidence: 99%
“…Tamrat et al [21 ▪▪ ] suggest trying to assess for subclinical dysfunction using LV strain in a similar method to how LV dysfunction is assessed in the presence of cardiotoxic chemotherapy. They looked at global longitudinal strain (GLS) and global circumferential strain (GCS) and found that these measurements were able to identify subclinical dysfunction prior to the development of LV dysfunction and symptomatic HF, but that further work will need to be done to use it as a screening tool.…”
Section: Step 3: Extra (Selected Patients)mentioning
confidence: 99%